1973
DOI: 10.1111/j.1476-5381.1973.tb08335.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin, catecholamines and cyclic AMP on calcium storage in aortic microsomes

Abstract: Summary1. The binding of calcium observed in microsomal membranes derived from the intimal-medial layer of rabbit aorta was specifically increased by the magnesium salt of adenosine triphosphate (Mg-ATP). This calcium uptake was inhibited by potassium and sodium. 2. Angiotensin II, both in the presence and in the absence of Mg-ATP, reduced the binding of calcium and increased the release of membraneincorporated calcium. These effects were dose-dependent. Analogues of angiotensin II devoid of intrinsic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Andersson and Nilsson (11), using the microsomal fraction from rabbit colon, found that the Ca-accumulating capacity of the microsomal fractions was potentiated by cyclic AMP. Similar findings were also reported in the microsomal fractions from rabbit aorta (12) and from rat uterus (13). Therefore, potentiation of the Ca-binding in the microsomal fractions, as induced by papaverine may be due to elevation in the levels of cyclic AMP with the inhibition of phosphodiesterase.…”
Section: Methodssupporting
confidence: 77%
“…Andersson and Nilsson (11), using the microsomal fraction from rabbit colon, found that the Ca-accumulating capacity of the microsomal fractions was potentiated by cyclic AMP. Similar findings were also reported in the microsomal fractions from rabbit aorta (12) and from rat uterus (13). Therefore, potentiation of the Ca-binding in the microsomal fractions, as induced by papaverine may be due to elevation in the levels of cyclic AMP with the inhibition of phosphodiesterase.…”
Section: Methodssupporting
confidence: 77%
“…Tomiyama and Hurwitz (26) reported that papaverine and aminophylline appear to exert their principal actions on cellular processes that remove Ca ions from the cytoplasm. It was reported that papaverine and dibutyryl cyclic AMP augment Ca efflux from smooth muscle cells and Ca uptake by microsomal fraction (15,17,27). Consequently it is conceivable that the nonspecific inhibition by papaverine and theophylline is at least in part mediated by cyclic AMP.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers reported that epinephrine, iso prenaline and papaverine, which increase intracellular levels of cyclic AMP, increased 45Ca-uptake by the microsomal fractions from some smooth muscles (4,14,26,27). On the other hand, some smooth muscle relaxants, which have no influence on the intracellular levels of cyclic AMP, inhibited 45Ca-uptake by the intestinal microsomal fractions (13, 27 29).…”
Section: Discussionmentioning
confidence: 99%